STRUKTUR GEOLOGI BAWAH PERMUKAAN DANGKAL BERDASARKAN INTERPRETASI DATA GEOLISTRIK, Studi Kasus Sesar Palu Koro - Marjiyono Marjiyono; H Kusumawardhani; A Soehaimi (Pusat Survei Geologi, 2013)
The existence of the Palu-Koro Fault, as an active lateral fault, has no doubt. Beside seismicity indications, geodetic observations has also proved the movement of this fault. However, subsurface studies in this section is not yet widely performed. Observation of geoelectric resistivity in Palu-Koro Fault zone has been performed at several sites around of this section. Results of analysis showes the presence of fault structures observed from offsetted bedrock as step over fault.Keywords : geoelectric, resistivity, Palu-Koro Fault, step over fault.